الکتاب أداة للتشکیل والتحویل الایدلوجى :دراسة ببلیوتاریخیة تحلیلیة للحالة المصریة فى الحقبیتین الاشتراکیة الناصریة والانفتاحیة الساداتیة - د. أمجد جمال حجازى (المجلة الدولية لعلوم المكتبات والمعلومات)
A Study adopts the Biblio-Historical Analytical Method in order toidentify the role that the “Book” had played in the ideological formation andconversion in two periods of the history of modern Egypt namely theNasser's Socialism and the Sadat's Openness, The study monitored 703books in the two subjects of socialism and openness between 1945 to1985. The study found that the Nasser's Socialism period largelydepended on the “Book” as a tool for the formation of the Egyptian societyby the ideology of socialism, while the period of Sadat's Openness sawweakness in relying on the “Book” as a tool to conversion the Egyptiansociety towards the ideology of openness